Jean-Léon Beauvois (1943–2020): A Key Figure in Social Psychology. Issue 1 (13th January 2021) - Dubois, Nicole; Pansu, Pascal
In this paper, we aim to illustrate how Jean-Léon Beauvois's work influenced developments in social psychology. We cannot cover every aspect of his work, but we will try to convey the strength of his commitment to science. His vision of human beings left little room for subjective or individual variables. His was a « behavioral and materialistic » vision. He believed that individual human thoughts and behaviors were rooted in social structures. The practices found inside these social structures, especially the evaluative practices to which an individual must submit him or herself, allow a person to develop cognitively as a social agent. Consequently, he or she totally adopts the model of individual differences and the belief system of the social structure to which he or she belongs. Jean-Léon Beauvois believed that these social practices created the mold in which sociocognitive processes took shape and ultimately produced naive knowledge as opposed to scientific knowledge.